2010
DOI: 10.5271/sjweh.2895
|View full text |Cite
|
Sign up to set email alerts
|

Associations between work-related factors and specific disorders of the shoulder – a systematic review of the literature

Abstract: van Rijn RM, Huisstede BMA, Koes BW, Burdorf A. Associations between work-related factors and specific disorders of the shoulder -a systematic review of the literature.literature. . Scand J Work Environ Health. 2010;36(3):189-201.Objective Our aim was to provide a quantitative assessment of the exposure-response relationships between work-related physical and psychosocial factors and the occurrence of specific shoulder disorders in occupational populations.Methods A systematic review of the literature was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
202
2
14

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 366 publications
(231 citation statements)
references
References 41 publications
(76 reference statements)
13
202
2
14
Order By: Relevance
“…As a multidimensional instrument, the work ability index (WAI) has been associated with musculoskeletal pain, chronic disease, productivity, sickness absence, early retirement and all-cause mortality (7)(8)(9)(10)(11). Additionally, workers exposed to highly repetitive and forceful exertion, lack of sufficient recovery, and awkward postures (12,13) have an elevated risk of both impaired work ability and musculoskeletal disorders (14)(15)(16). To prevent premature exit from the labor market, effective occupational interventions to prevent deterioration of work ability among employees with high physical work demands are warranted.…”
mentioning
confidence: 99%
“…As a multidimensional instrument, the work ability index (WAI) has been associated with musculoskeletal pain, chronic disease, productivity, sickness absence, early retirement and all-cause mortality (7)(8)(9)(10)(11). Additionally, workers exposed to highly repetitive and forceful exertion, lack of sufficient recovery, and awkward postures (12,13) have an elevated risk of both impaired work ability and musculoskeletal disorders (14)(15)(16). To prevent premature exit from the labor market, effective occupational interventions to prevent deterioration of work ability among employees with high physical work demands are warranted.…”
mentioning
confidence: 99%
“…The fact that the exposure was self-reported must also be discussed: the authors of a recent review of shoulder disorders and occupational factors stated that in 29% of the selected studies, only questionnaires were used for the assessment of exposure (10). However, the description of the lifetime exposure to physical workload in various socioprofessional groups suggested that self-reported exposure was probably accurate, especially "hands above shoulders" and manual handling (20).…”
Section: Discussionmentioning
confidence: 99%
“…Repetitiveness and exposure to vibration were not available. Psychosocial factors were not studied given that there is insufficient evidence to conclude a relationship between shoulder disorders and these factors (10,31) The main purpose of this study was to analyze the long-term determinants of severe shoulder pain among men, especially the role of arm elevation >90° while carrying loads. Our results tend to confirm that the factors associated with severe shoulder pain at baseline might be risk factors (or aggravating factors) in the long-term and even after retirement (ie, after cessation of exposure).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations